Pengaruh Digital Marketing, Kepercayaan, Dan Inovasi Terhadap Loyalitas Konsumen Maxim Di Kota Batam - Setiawan Fau; M Khoiri (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2024)
This research aims to explore the influence of digital marketing, trust and innovation on Maxim consumer loyalty in Batam City. The population in this study focuses on individuals who act as consumers, who have used Maxim's services during 2023, the exact number of which cannot be known. The research sample of 204 respondents was selected using the Jacob Cohen formula with withdrawals based on purposive sampling. The data analysis process involved a series of steps in multiple linear regression, which includes data quality testing, classical assumption testing, and hypothesis testing. The results of multiple linear regression analysis indicate that digital marketing has an influence of 35.3% on consumer loyalty. Trust has an influence of 30.9% on consumer loyalty. Innovation has an influence of 22.5% on consumer loyalty. The findings of the analysis of the coefficient of determination (R2) obtained confirm that overall digital marketing, trust and innovation are able to explain as much as 56.3% of the variation in consumer loyalty. Apart from that, through the t test and F test, results were obtained which confirmed that digital marketing, trust and innovation have a positive and significant influence, both partially and simultaneously, on Maxim consumer loyalty in Batam City.